Plants : their use, management, cultivation and biology:a comprehensive guide - Watson, Bob , 1948- (Crowood Press, 2008)
Filled with biological information about plants as well as practical and instructional advice about how to grow and nurture them, this work covers soft plants, shrubs and woody climbers and discusses a range of both British native and exotic plants found elsewhere throughout the world. It also gives an introduction to the diversity of plants.